3 | 3 ... -6 ... -8 ... -19
.. | .. ... 9 .. 9 .... 3
- - - - - - - - - - - - - - - -
.. | 3 ... 3 ... 1 .... -16
which means
[tex]\dfrac{3x^3-6x^2-8x-19}{x-3}=3x^2+3x+1-\dfrac{16}{x-3}[/tex]
which is to say that [tex]p(x)[/tex] is not divisible by [tex]x-3[/tex], and so [tex]x=3[/tex] is not a root. This in turn means [tex]p(k)\neq0[/tex].
Indeed, you have
[tex]p(3)=3(3)^3-6(3)^2-8(3)-19=81-54-24-19=-16[/tex]
If you were familiar with the polynomial remainder theorem, you would have known this immediately from determining the remainder alone.